2012
DOI: 10.1080/00987913.2012.10765470
|View full text |Cite
|
Sign up to set email alerts
|

Broken-Link Reports from SFX Users: How Publishers, Vendors and Libraries Can Do Better

Abstract: This study analyzes more than 400 SFX broken-link reports sent by users of an academic library. It raises technical issues regarding OpenURL linking in the handling of special journal volume and issue numbers, journal supplemental issues, embargo release dates, book reviews, DOIs, and other areas. It reports on full-text resources with the most broken links, causes of broken links, and the library's responses to users. It also explores how journal publishers, database vendors, and OpenURL vendors can improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Chen's study of SFX dead-link reports found a variety of errors causing these reports: the articles really were not available; index errors such as incorrect citations; links that go to the journal only; links go to book reviews or other special items; abnormal volume, issue, or page numbers, especially with articles in supplemental issues; confusion between online publication date and official publication date; DOI errors; and missing online content. 38 Presentation and Identification of E-Journals (PIE-J) is an emerging standard that makes recommendations that address some of these issues: publishers should present content under the original journal title, instead of putting all online content under the latest title; the print and online ISSNs should be displayed; publishers should use clear and consistent numbering schemes. 39 OpenURLs dynamically link users from citations to library holdings and have been widely adopted by librarians and information providers.…”
Section: Electronic Resource Management and Discoverymentioning
confidence: 99%
“…Chen's study of SFX dead-link reports found a variety of errors causing these reports: the articles really were not available; index errors such as incorrect citations; links that go to the journal only; links go to book reviews or other special items; abnormal volume, issue, or page numbers, especially with articles in supplemental issues; confusion between online publication date and official publication date; DOI errors; and missing online content. 38 Presentation and Identification of E-Journals (PIE-J) is an emerging standard that makes recommendations that address some of these issues: publishers should present content under the original journal title, instead of putting all online content under the latest title; the print and online ISSNs should be displayed; publishers should use clear and consistent numbering schemes. 39 OpenURLs dynamically link users from citations to library holdings and have been widely adopted by librarians and information providers.…”
Section: Electronic Resource Management and Discoverymentioning
confidence: 99%
“…University of Texas Southwestern Medical Library researchers Jayaraman and Harker (2009) tested 380 randomly selected citations from A&I databases where full-text was known to exist in another subscribed resource, and found that Ebsco LinkSource failed to make the connection 9% of the time (above their target 5% goal). Chen (2012) categorized 432 linking errors reported by Bradley University patrons over a four year period, and found that the most common reasons for link failure involved missing content, incorrect metadata, or knowledge base collections that did not support article level linking. Finally, Stuart, Varnum and Ahronheim (2015) analyzed 430 user-reported errors and randomly tested over 2,000 OpenURLs from University of Michigan link resolver log files over a three year period, concluding that OpenURLs failed with a discouraging 20% frequency.…”
Section: Literature Reviewmentioning
confidence: 99%